Phosphatidylinositol metabolism in cells transformed by polyomavirus middle T antigen. - Ulug, E T (1990)
Associated with the middle T antigen of polyomavirus is a novel phosphatidylinositol (PtdIns) kinase activity which phosphorylates PtdIns at the D-3 position of the inositol ring. We have undertaken an analysis of myo-[3H]inositol-containing compounds in a panel of NIH 3T3 cell lines stably transfected with transforming and nontransforming middle T antigen mutants. All cell lines from which PtdIns 3-kinase activity coprecipitated with middle T antigen exhibited modestly elevated levels of PtdIns(3)P and compounds with predicted PtdIns(3,4)P2 and PtdIns(3,4,5)P3 structures. Complex formation between middle T antigen and PtdIns 3-kinase correlated not with an increase in total inositol phosphate levels but rather with elevated levels of InsP2 and InsP4. A specific increase in the level of an InsP2 species which comigrated in high-pressure liquid chromatography analysis with Ins(3,4)P2 was observed. These results suggest that association of the polyomavirus middle T antigen with PtdIns 3-kinase activates a distinct inositol metabolic pathway.